Impact of Moisture Content on the Dynamic Failure Energy Dissipation Characteristics of Sandstone - Aihong Lu; Shanchao Hu; Ming Li; Tianzhu Duan; Bing Li; Xiya Chang (Shock and Vibration)
Rockburst frequently occurs in deep underground engineering, which poses a threat to safety and causes economic losses. Water injection into surrounding rock masses is an effective method for preventing rockburst, and the moisture content of rocks is significant for assessing the probability of rockburst. However, the majority of studies focus on the relationship between the macromechanical properties of rock masses under static loads and the moisture content of rock masses and seldom explore the impact of moisture variation (under dynamic loads) on the mechanical properties and energy dissipation. In this paper, the mechanical properties and energy dissipation of sandstone with different moisture contents have been experimentally investigated by the split Hopkinson pressure bar (SHPB) test. The test results indicate that the peak strength, dynamic elastic modulus, and unloading elastic modulus of sandstone in dry conditions are considerably larger than those in moisture conditions, and the three parameters linearly decrease as the moisture content increases from 0% to 2.58%. The distribution law of sandstone fragments with different moisture contents has been investigated by sieving test fragments with different grain sizes of grading sieves. The results show that the percentage of large grain size fragments incrementally decreases, and the percentage of small grain size fragments incrementally increases with moisture contents from 0% to 2.58%. When the moisture content ranges from 2.01%∼2.58%, the fractal dimension linearly increases, which indicates that the higher the moisture content is, the larger the dimension of the broken sandstone is. The calculation results for energy indicate that the sandstone energy attains the peak value with 0% moisture content. When the moisture content ranges from 2.01%∼2.58%, the reflected energy increases, and the transmitted energy and dissipated energy linearly decrease. In addition, the surface energy of the sandstone with different moisture contents has been investigated by converting fragments into spheres with the corresponding size. The results indicate that the smallest surface area of sandstone is obtained in dry conditions, but its surface energy in dry conditions is larger than that in moisture conditions. When the moisture ranges from 0% to 2.58%, due to 3% illite and 2% chlorite clay minerals reacting with different proportions of moisture, the surface areas of sandstone fragments linearly increase and the surface energy of sandstone linearly decreases.